2021
DOI: 10.4067/s0717-97072021000305295
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Mixed Ligand Metal Complexes Of Cu(II), Ni(II), And Zn(II) Ions: Synthesis, Characterization, Antimicrobial And Antioxidant Properties

Abstract: A series of transition metal complexes having general formula [M(L1)(L2)](NO3)2, (where, M = Cu(II), Ni(II), and Zn(II)) of mixed ligands, L1 = Isonicotinamido-Thiophene-2-Carbaldimine, L2 = 1, 10-phenanthroline, were synthesized. The obtained compounds were successfully characterized by different spectroscopic techniques. Conductivity measurements indicated that all complexes were 1:2 electrolytes in nature. IR spectra indicated that ligands coordinated to metals via the carbonyl oxygen atom and the azomethin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…According to the findings, all of the metal complexes showed moderate DPPH radical scavenging activity (Figs. [13][14]. The order can be expressed as BHT> CuL1> NiL1> ZnL1>L1.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the findings, all of the metal complexes showed moderate DPPH radical scavenging activity (Figs. [13][14]. The order can be expressed as BHT> CuL1> NiL1> ZnL1>L1.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…It is well known that metal complexes obtained from isoniazid-based Schiff bases exhibit greater antibacterial activity than isoniazid as well as free ligands. The anti-oxidant action of the Schiff base is further improved when it is coordinated with transition metal ions [14].…”
Section: Introductionmentioning
confidence: 99%
“…This focus stems from the recognition that oxidative stress and the detrimental effects caused by free radicals play a role in various pathological conditions such as cancer, cardiovascular diseases, neurodegenerative disorders, and the aging process. [11,12] The evaluation of the antioxidant potential of metal complexes derived from Schiff bases entails investigating their capacity to scavenge free radicals, inhibit oxidative reactions, and shield biomolecules from oxidative damage. These assessments commonly employ various in vitro assays, including the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging, ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)) radical cation decolorization, superoxide radical scavenging, lipid peroxidation inhibition, and DNA damage protection assays.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant research efforts have been devoted to assessing the antioxidant capabilities of these metal complexes. This focus stems from the recognition that oxidative stress and the detrimental effects caused by free radicals play a role in various pathological conditions such as cancer, cardiovascular diseases, neurodegenerative disorders, and the aging process [11,12] …”
Section: Introductionmentioning
confidence: 99%
“…Many mixed ligand-complexes of transition metals have demonstrated a wide range of biological properties. These biologically important metal ions and their mixed ligand complexes have also been linked to the activation of several enzymes [ 12 ], transportation of active molecules through membrane and storage [ 13 ]. It was extensively reported that transition metal mixed ligand complexes are employed in treating microbial infections because they are shown to be more biologically active than the ligand alone and its binary complexes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%